HOW TEACHING METHODOLOGY SHAPES CLASSROOM INTERACTION. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This paper explores the significant role of teaching methodologies in shaping classroom interaction. Effective teaching strategies not only facilitate the transfer of knowledge but also influence student engagement, participation, and communication. By analyzing various approaches, including traditional, communicative, and technology-assisted methods, this study highlights how different methodologies impact teacher-student and student-student interactions, fostering a dynamic and productive learning environment.